Four-element MIMO antenna for X-band applications. Issue 8 (7th October 2021) - Eslami, Ali; Nourinia, Javad; Ghobadi, Changiz; Shokri, Majid
Abstract: This study presents a new design of a four-element multiple-input multiple-output (MIMO) antenna, which is suitable for X-band applications. The circular polarization (CP) operation in this work is attained by using Tai Chi-shaped patches and L-shaped feeds. The proposed four-element MIMO antenna achieves two resonant frequencies, the first one at around 7.75 GHz and the second one with CP radiation is at approximately 10.15 GHz frequency. The measured isolations between ports with 46.7 × 46.7 mm 2 total dimensions are <−20 dB. Due to the experiments, the envelop correlation coefficient for the orthogonal and parallel ports of the proposed MIMO antenna is <0.003 and 0.005, respectively. Additionally, the presented antenna has a circularly polarized performance in the frequency band of 9.75–10.41 GHz and the average realized peak gain almost 2 dBic. The investigated antenna in this work is fabricated and tested in which the results are in a good agreement.